Effect of trehalose on the stability of dehydrated surimi-based fish cake during ambient storage - Inolino, Reyda I.
Surimi-based products are commonly preserved by freezing. Among them is fish cake which rely on low temperature storage to increase shelf life. However,, this method of preservation require high capitalization due to high cost for the facilities and the electricity required in running the equipment. Drying is a widely used method of preservation to extend shelf life of the product. However, drying can cause protein denaturation due to aggregations of protein when water is removed from the matrix. Thus, this study will assess the effect of the addition of trehalose on the stability of dehydrated fish cake during processing and storage. Products were stored at ambient condition for 90 days and evaluated for sensory acceptability, physic-chemical changes (folding test, rehydration ratio, water holding capacity and pH) and microbial growth (total plate count and mold count). The result of the study revealed that 6% trehalose concentration showed a better protective effect on the quality of dehydrated fish cake compared to other treatments due to its effect on the protein denaturation when dehydrated fish cake is stored at ambient condition. Dehydrated fish cake with 6% and 4% trehalose concentrations remained stable and safe for human consumption at 90 days ambient storage.